Analisis Pendapatan Kandang Closed House (Studi Kasus kandang Closed House Welkin Situmorang) di Bulik Kabupaten Lamandau Provinsi Kalimantan Tengah - Rido, Muhammad; Erni, Nurliani (CV. Utility Project Solution, 2023)
The purpose of this study is to analyze the income analysis and production performance of broiler chickens kept in a closed-house cage by Pak Welkin Situmorang. The production performance of broiler chickens, including final body weight growth, ration consumption, and FCR, were the factors observed in this study. Moreover, a variable revenue, variable cost, and variable income income analysis. Both descriptive analysis and quantitative analysis techniques were used to examine the research data. The broiler performance study's findings revealed that the average final body weight per head was 1.95 kg, the average ration consumption per head was 2.9 kg, and the average FCR value was 1.56 kg. The results of the income analysis also take the form of average costs of Rp. 528,675,000, average revenues of Rp. 595,107,000, and average incomes of Rp. 66,432,000. In conclusion, the broilers kept at Pak Welkin's Closed House produced well, with an average harvest age of 30.7 days, an average harvested body weight of 1.84 kg/head, a period-to-period ration consumption of 2.9 kg/head, and an average FCR value of 1.56. The broiler performance at Pak Welkin's Closed House was determined to be classed as very good because all production performance indicators met the standards that were established. With an average revenue of IDR 66,432,000 and a return on capital (R/C) ratio of 1.13, Mr. Welkin's Closed House is already profitable.